Pelatihan Pembuatan Ecoprinted Totebag sebagai Materi Prakarya Ramah Lingkungan bagi Siswa Sekolah Dasar - Septian Ragil; Hadi Saptiono; Riska Rahmawati; Mohamad Nasirudin; M Farid Nasrulloh; M Aliyul Wafa; Salim Ashar; Saihul Atho’ A’laul Huda (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2023)
The purpose of community empowerment in this training is the researcher invites students or partners to make motifs on tote bags (tote bags) using the Eco print technique. The Service Learning approach is a method in this training process. The Service Learning approach aims to shape the personality of the younger generation who are able to solve problems, manage emotions, be able to work in a work team, and have a respectable identity. Through the Service Learning project, students are very enthusiastic about working and feel proud because they can make their own work and innovate with their own mindset. Service Learning activities are actualized in the form of training on making Eco print tote bags. Through this training, students can express joy and pride about what they do. From the results of the questionnaire regarding students' initial understanding regarding the Eco print technique, it was found that only 1 student had made batik crafts, but none of the students had heard of or made the Eco print technique. This caused all students who participated in this activity to feel interested and want to be creative by using leaves as a medium for giving colors and motifs to the Eco print technique. Of all the aspects evaluated, the average score is "yes", which shows that the workshop and training activities for making Eco print tote bags are running and well received. Based on the results of the activities that have been carried out at this time, there is great hope for researchers that schools can carry out the continuation of this program because this activity is very useful for developing students' talents and creativity in the field of works of art.